Educação financeira: uma abordagem centrada na modelagem matemática - Souza, Ricardo Antonio de (2018)
In recent years, we have noticed a large increase in the number of families in Brazil, thinking about how to contribute to the improvement of this situation, we decided to develop this research, which seeks to verify if financial mathematics, when developed by mathematical modeling as a teaching and learning strategy, can contribute to the development of students' financial behavior in a higher technology course in logistics and computer science. In the present research, we hypothesize that when financial mathematics is developed using this strategy, there is a positive influence on the understanding of the content worked and, consequently, influences the financial behavior of the subject. In order to validate our hypothesis, we use the modeling processes, which brings the student closer to the real scientific activity, that is, the student becomes a researcher, testing conjectures, formulating hypotheses, proving, constructing models, concepts, theories and socializing the results. According to this strategy, it is up to the teacher to provide favorable situations, so that the student in this effective action on knowledge, transform it into knowledge in this process of scientific search. Recent research shows that students who have already completed the discipline of financial mathematics in an undergraduate course usually do not use or associate the studied content with their financial life, so we try to answer the following research question: The use of mathematical modeling as a strategy for teaching and learning Financial Mathematics, could contribute to the development of Financial Education ?. As well as the following specific questions: What evidence of financial literacy can be identified after a training on Financial Mathematics centered on the modeling approach? What contributions of mathematical modeling can be identified for the construction of financial literacy? To answer them, we created a questionnaire to be applied to students of two technology courses of a public institution of higher education, located in the great ABC - SP. Being the first, technology in logistics and the second in computing. The students of the first course answered the questionnaire after attending a financial mathematics workshop, structured by mathematical modeling. In order to have a comparative parameter of answers, we apply the same questionnaire to students of the second course, but these without participating in the workshop of financial mathematics. With the answers given to the questionnaire, we performed a cohesive analysis with the help of the CHIC software, and identified traits of development of financial education by our target audience